Child and parent perspectives on healthier side dishes and beverages in restaurant kids' meals: results from a national survey in the United States. - Shonkoff, Eleanor T.; Anzman-Frasca, Stephanie.; Lynskey, Vanessa M.; Chan, Grace.; Glenn, Meaghan E.; Economos, Christina D. (2017)
Background: Children frequently consume foods from restaurants; considering the quick-service sector alone, 1/3 of children eat food from these restaurants on a given day, and among these consumers, 1/3 of their daily calories come from fast food. Restaurant foods and beverages are second only to grocery store foods and beverages in their contribution to total energy intake of U.S. 4- to 11-year-olds. Shifting their restaurant consumption in healthier directions could have a positive impact on child health. In 2014 this study examined self-reported child receptivity and parent awareness of child receptivity to ordering a fruit or vegetable side dish instead of French fries; and milk, water, or flavored water instead of soda/pop with a kids' meal when eating out. Child receptivity to side dishes was compared between 2010 and 2014.; Keywords: Nutrition, Restaurants, Children, Kids' meals, Fruits/vegetables, Side dishes, Beverages, Restaurant menus, Parents.; Springer Open.